CULTURAL INTELLIGENCE IN THE DIVERSITY OF SCIENCE - Nugraha, Agung (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2019)
The purpose of this paper is to conceptually and empirically analyze cultural intelligence from a variety of perspectives. Intensive conceptual and empirical studies of the trends in the dynamics of cultural intelligence in the perspective of the fields of psychology, sociology and organization are the research methods used. This paper is expected to contribute to the development of science in the field of multicultural services, especially cross-cultural guidance and counselling services. This paper is then expected to be one of the treasures of developing multicultural competencies in the implementation of guidance and counselling services.